MODELING AND FORECASTING OF LENTIL PRODUCTION IN INDIA AND ITS INSTABILITY - Supriya; Aditya Bhooshan Srivastava; Yashpal Singh Raghav; Monika Devi; Sachin Kumar Verma; Diks; Aditya Bhooshan Srivastava; Yashpal Singh Raghav; Monika Devi (Journal of Animal and Plant Sciences, 2023)
India is a major producer of pulses around the world, which constitute an essential component of vegetarians' protein-rich diets in India. The present study attempts to apply the autoregressive integrated moving average (ARIMA) and Holt linear trend model approach to investigate lentil production trends in Bihar, Madhya Pradesh, Uttar Pradesh, West Bengal, and India. Yearly data were collected from Agriculture Statistics at a glance, 1970 to 2019 were used for forecasting up to 2029. In comparison, the ARIMA model is the best for prediction based on the maximum value of R2 and lowest value of MAPE, MPE, RMSE, and MAE. The results showed that ARIMA (1,1,5) model for Bihar, ARIMA(0,1,4) model for Madhya Pradesh, ARIMA (0,1,5) for Uttar Pradesh, ARIMA (0,1,4) for West Bengal, and ARIMA (0,1,2) for India was found suitable to forecast the future of lentil with an 80% and 95% accuracy level and according to the analysis of instability, the instability is increasing in all three states and India, but the instability was decreasing in Uttar Pradesh. While in the decomposition analysis the area effect was an essential factor for the change in lentil production in Bihar, Madhya Pradesh, West Bengal, and India, but in Uttar Pradesh the yield effect was responsible during the overall periods. Besides this research will be essential to determining the future gap between pulse production and demand.
Keywords: ARIMA; Decomposition; Forecasting; Holt’s linear trend; Instability and lentil production